SOOTHER TRIAL: Observational study of an over-the-counter ointment to heal anal itch - Felemovicius, Isaac; Ganz, Robert A.; Saremi, Mohammad; Christopfel, William (Frontiers in Medicine, 2022)
Introduction Pruritus ani, or rectal or anal itch, is a common perianal disorder that affects ~5% of the population of the developed world. Treatments for this disorder are somewhat limited and include conservative non-medical perianal hygiene care, and topical medical treatments including topical steroids, antibacterial and antifungal agents, and topical anesthetic/analgesics such as lidocaine or capsaicin; astringents and vasoconstrictors such as ephedrine can also be used. Methods The study was IRB approved. We assessed the efficacy of a novel, composite, over-the-counter, topical lidocaine ointment that included an epidermal barrier and antimicrobial effect along with the typical lidocaine anesthetizing effect, in a single arm, observational, longitudinal, population of 20 ambulatory pruritus ani patients. Patients applied the ointment twice daily, and were studied for 2 weeks; primary outcomes included time to symptom resolution and clinical exam resolution as measured on a 5-point visual analog scale. Results Twenty-nine consecutive patients were screened and 20 patients (12 males; 8 females) were enrolled in the study. Ninety percent of patients achieved 100% symptom resolution by 2 weeks, and most were improved within 72 h of initiating treatment; 95% of patients had a normal visual exam by the 2 week endpoint. There were no significant adverse events attributable to the therapy. Conclusion Use of a novel composite topical lidocaine agent, demonstrated rapid and effective relief of pruritus ani in an ambulatory population. Additional studies are underway. Clinical trial registered Clinicaltrials.gov, identifier NCT05288907.